Manajemen Keuangan untuk Ibu-Ibu Binaan Taman Bacaan Perigi, Depok - Benarda Benarda; Sevty Wahiddirani Saputri; Siarwi Siarwi; Fathudin Ali; Heri Iswanto (Abdimisi, 2021)
Mothers are a local movement that grew from, by and for the community. with women as the main driving force in creating a happy, prosperous, and independent family. Improving the quality of women is also through programs to develop and utilize the various potentials that exist in women. The purpose of this community service is to provide knowledge, and understanding of financial management, and fund management among housewives. This community service method is seminars and discussions. The population in this community service activity is as many as 25 housewives who are members of the Perigi Reading Park in the Depok area. The result of this community service is that all participants can manage their finances well, and are motivated in entrepreneurship so that they can create new jobs.